FORMATION OF PEDAGOGUE'S STRESS RESISTANCE - Alexander Volkov; Olga Chursinova; Gemma Gasparyan (Вестник Северо-Кавказского федерального университета, 2022)
The article describes the main approaches to the concept of «stress». Stress is the key to the preservation, development and strengthening of mental and physical health of a person, so the teacher must master the skills of controlling your emotions in order to maintain health under stressful conditions. The authors have developed and described a model of formation ofstress a teacher, includes four major blocks: target, substantial, procedural, effective.